Root canal and fiber post treatment of maxillary right lateral incisor with pulp necrosis and periapical lesion due to secondary caries: Perawatan saluran akar dan pasak fiber pada gigi incisivus lateral kanan maksila nekrosis pulpa dengan lesi periapikal akibat karies sekunder - Ilma Yudistian (Makassar Dental Journal, 2022)
Secondary caries can occur due to microleakage at the edge of the restoration followed by invasion of micro-organisms and sa-liva through the dentinal tubules; if left untreated, causes pulp necrosis. The aim of this article is to provide information on root canal treatment with fiber post restorations and composite restorations in pulp necrosis teeth due to secondary caries. A 17-years-old male patient came to dental clinic complaining of a pain in his upper right anterior tooth since 2 weeks ago. The tooth was filled with tooth-colored filling 1 year ago. The clinical examination, tooth 12 necrosis and there was a composite restoration on the mesial to incisal part with a discoloration at the border of the restoration. The radiograph shows a radiolucent area at the apical of the tooth and a radiopaque area in the coronal surrounded by a radiolucent area. Open access was performed on the palatal area for subsequent root canal treatment and continued with fiber post insertion and direct restoration with composite resin. Control was carried out 6 months after the completion of treatment; the adaptation of the restoration edge was good and there were no complaints from the patient.